Peran Green Human Resource Management (GHRM) dalam Mendorong Keberlanjutan Industri Pariwisata dan Perhotelan di Bali - Rosid, Muhammad Abdul; Khaeriah, RD. Hera Merdeka Khazinatul; Abas, Sayid; Darojat, Ilma; Isrok, Isrok (Westscience Press, 2025)
This study explores the role of Green Human Resource Management (GHRM) in promoting sustainability within Bali's tourism and hospitality industry. Using a qualitative approach, interviews with five key informants reveal the adoption of GHRM practices, including green recruitment, training, performance management, and workplace initiatives. The findings highlight GHRM's significant contribution to environmental conservation, employee engagement, and organizational reputation, despite challenges such as resource constraints and resistance to change. The study underscores the importance of stakeholder collaboration to address barriers and optimize GHRM’s potential. These insights provide valuable implications for the sustainable development of Bali's tourism sector.